Metamaterials with asymmetric transmission effect based on magnetic field manipulation - Jiaqi Cui; Haochen Yan; Yuzhen Lou; Xiaoyuan Huang; Qi Zhu (Scientific Reports, 2025)
Abstract Realization of asymmetric transmission (AT) effect in metamaterial has drawn great interest in the past decade years since it indicates broad applications such as isolators and chiral polarization transistors which are highly demanded in various areas. However, most realization of AT is through the manipulation of electric field in chiral metamaterial, which limits the applications in the regimes requiring magnetic responses. In this article, we propose a metamaterial with chiral structure composed of connected metal loops placed on orthogonal directions, where the response orthogonal to the magnetic field of incident electromagnetic wave can be generated. Such manipulation of magnetic field is quantified with the equivalent permeability tensor of the metamaterial. The presented material exhibits AT characteristics of linear polarized electromagnetic wave sensitive to both polarization directions and propagation directions. Our work provides a new approach for AT, which has potential application of polarization sensitive devices, such as polarization rotators and circular polarizers.